Factors Influencing the Teaching and Learning of Igbo Language in Secondary Schools in Onitsha North Local Government Area of Anambra State Nigeria - Ann Ngozi Ugobueze (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: The Igbo language, as one of Nigeria's major indigenous languages, faces challenges in its effective transmission to younger generations. Despite its cultural and academic importance, its teaching and learning in secondary schools encounter various obstacles that affect students’ proficiency and interest. Objective: This study aims to examine the key factors influencing the teaching and learning of the Igbo language in secondary schools in Onitsha North Local Government Area, Anambra State, Nigeria. Method: A descriptive survey design was employed. Data were collected from both teachers and students through structured instruments to capture the diverse elements affecting language instruction and acquisition in real classroom contexts. Result: The findings indicate that teacher qualification significantly impacts student performance, with trained Igbo language specialists contributing positively to academic achievement. However, challenges such as lack of instructional materials, insufficient time allocation for language instruction, and mother-tongue interference hinder effective teaching. Additionally, the home environment presents mixed influences while parental support can enhance learning, the prevalent use of non-standard Igbo at home may impede correct usage and understanding.  Conclusion: Improving the teaching and learning of Igbo requires addressing both in-school and out-of-school factors. Emphasis must be placed on teacher training, provision of teaching resources, and balanced time management, alongside fostering supportive and linguistically rich home environments. Contribution: This study contributes to the growing body of research on indigenous language preservation and education. It provides practical insights for policymakers, educators, and curriculum planners to develop targeted interventions that strengthen Igbo language education and encourage its sustained use among younger generations.